Paroxysmal drastic abdominal pain with tardive cutaneous lesions presenting in Henoch-Schnlein purpura - Xiao-Liang Chen Hong Tian Jian-Zhong Li Jin Tao Hua Tang Yang Li Bin Wu (世界胃肠病学杂志：英文版, 2012)
Henoch-Schnlein purpura（HSP） is a small-vessel vasculitis mediated by IgA-immune complex deposition.It is characterized by the clinical tetrad of non-thrombocytopenic palpable purpura,abdominal pain,arthritis and renal involvement.The diagnosis of HSP is difficult,especially when abdominal symptoms precede cutaneous lesions.We report a rare case of paroxysmal drastic abdominal pain with gastrointestinal bleeding presented in HSP.The diagnosis was verified by renal damage and the occurrence of purpura.